A NOTE ON COMPATIBLE BINARY RELATIONS ON VECTOR VALUED HYPERSEMIGROUPS - Miovska, Valentina; Celakoska-Jordanova, Vesna (Matematichki Bilten, 2017)
In this note we present some properties concerning the connection between vector valued hypersemigroups and various kinds of compatible binary relations defined on them, i.e. \(i\)-compatible, compatible, strongly \(i\)-compatible, strongly compatible, regular and strongly \(i\)-regular binary relations.